Makna Simbolik Rumah Sebagai Ekpresi Kultural Pada Masyarakat Hindu dan Islam di Linggo Asri - Muhammad Khasanul Huda (IQTIDA : Journal of Da'wah and Communication, 2024)
This research focuses on Hindu and Islamic communities in Linggo Asri Village, Indonesia, using case study methods and communication sociology and anthropological approaches. Through observations, interviews and documentation studies, research shows that a house is not just a physical place to live but reflects cultural substance. Religious symbols, such as prayer houses and prayer rooms, are not only places of worship but also means of communication between religious believers. The Linggo Asri community understands differences in beliefs and finds common ground in gratitude for diversity. Analysis of religious practices, such as Pedhayangan and Slametan, shows that the essence of these practices is universal even though there are differences in terminology and rites. Research highlights the importance of pluralism and tolerance in Linggo Asri, where religious differences become an enriching force and strengthen relations between religious believers. This article contributes to the understanding of religious diversity and religious symbols in Indonesian society. These religious practices and symbols reflect beliefs and are the basis for social harmony and tolerance between religious believers. Understanding and respect for religious differences is the key to creating an inclusive and peaceful society in rich diversity.